Influential Factors on Diffusion Bonding Strength as Demonstrated by Bonded Multi-Layered Stainless Steel 316L and 430 Stack - Liu, Da-Wei; Lin, Chun-Nan; Lin, Wei-Shuai; Lee, Shyong; Gwo, Jyh (Materials, 2024)
In this study, we optimized the parameters of diffusion bonding on multi-layered stainless steel 316L and 430 stacks. The preparation process for diffusion bonding is crucial, as the bonding surfaces need to be polished and meticulously cleaned to ensure a smooth bonding process. We fabricated twelve-layer plates consisting of 55 mm × 55 mm × 3 mm and 100 mm × 50 mm × 3 mm dimensions, and the bonding response was investigated by evaluating the tensile strength of the bonding zone under varying bonding conditions, with a bonding temperature ranging from 1000 to 1048 °C, a bond time ranging from 15 to 60 min, pressure ranging from 10 to 25.3 MPa, and under a vacuum environment. SS430 exhibits a significantly higher compression creep rate than SS316L. The compressibility of diffusion welding materials does not impact the diffusion bonding strength. Multi-axial tensile strength tests confirmed strong bonding joint strength in various axes. The tensile strengths of monolithic and Diffusion bonding (DB) specimens tested in parallel are essentially identical. The optimized diffusion bonding parameters (Condition G2C: 1048 °C/25.3 MPa/15 min) are ideal for producing SS316L stainless steel cores in compact heat exchangers, offering a superior bonding quality and reduced costs. These findings have practical implications for the production of stainless steel cores in compact heat exchangers, demonstrating the relevance and applicability of our research.